Analisis Perbandingan Kinerja Keuangan PT. GAS NEGARA Tbk dengan PT. ANEKA GAS INDUSTRI Tbk pada Periode Tahun 2020 - 2021 - Suparna Suparna; Sri Hermuningsih (Journal on Education, 2023)
This study aims to compare the financial performance between PT. GAS NEGARA INDONESIA Tbk and PT.ANEKA GAS INDUSTRI Tbk, for the 2021period,using liquidity ratios,activityratios,and profitability ratios. This research method use in this study is descriptive qualitative. Data collection techniques using literature and documentation by accesing the related web to obtain secondary data. the data analysis technique use use is liquidity ratio analysis, which consists of the current ratio, quick ratio, activity ratio, namely the account receivable turnover ratio and inventory. Turnover ratio while the profitability ratio consists of profit margin (PM), and return on asset ( ROA).the results of the study show that the overall financial performance of PT.GAS NEGARA INDONESIA Tbk, is better than the financial performance of PT.VARIUS GAS INDUSTRY Tbk. PT.GAS NEGARA INDONESIA Tbk, has more ability to pay its short term debt obligations and its long term liabilities compared to PT. VARIUS GAS INDUSTRY Tbk.based on the 2021 financial report, PT GAS NEGARA INDONESIA Tbk, LIQUIDITY RATIO, both the current ratio and the fast ratio, are recorded or more than 160%. Meanwhile, PT VARIUS GAS INDUSTRY Tbk, is more effective in collecting accounts receivable, compared to PT.GAS NEGARA INDONESIA Tbk and PT. VARIUS GAS INDUSTRY Tbk.Are experiencing positive performance growth in 2021. Because the two companies are able to record a steady profit.